Formulasi Spray Gel Ekstrak Daun Pandan Wangi Sebagai Antiseptik Tangan - Metha Anung Anindhita; Nila Oktaviani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Spray gel as an alternative to hand washing soap. Pandan wangi leaves are efficacious as antiseptics. This study aimed to obtain a good formulation of spray gel pandan wangi leaves extract and efficacious as an antiseptic. The method used in this study was to compare the concentration of Hydroxypropyl methylcellulose (HPMC) on three formulas including 0,5%; 1,5%; and 2,5%. The formulas was tested for their physical properties to determine the best formula and will be tested for physical stability at room temperature (28o±2oC) for 4 weeks and followed by testing the effectiveness of antibacterials. The result showed that formula I (0,5% HPMC concentration) was the best formula. This formula fulfills all the criteria for good physical properties. The formula I was stable at room temperature and has effectiveness against Staphylococcus aureus. This study is the basic experiment for development of spray gel prparations with active substances derived from natural ingredientsKeywords : mspray gel, Pandanus amaryllifolius, Roxb. extract, anseptic